Speaking without fear or nervousness - White, Winsor; Keller, Matthew A.; Foreman, Nancy; Sealy, Steve; Sutton, Helen (Milton Keynes : CareerTrack)
Volume 1 of the video, identify the fears at the core of speaking phobia and volume 2 specify remedies for physical symtoms such as a wobbly voice, shaky hands and a racing heart.
vol. 1 Conquer your fear - vol. 2 Overcome your physical symptoms
Video is accompanied by 1 workbook
Editor, Dale Hinkle, Kenny Allen
Trainer: Helen Sutton
Keywords: Communication; Voice